Impacts, strategies and tools to mitigate UHI - Leal Filho, Walter; Echevarria Icaza, Leyre; Omenche, Victoria; Al-Amin, Abul Quasem (A+BE | Architecture and the Built Environment, 2018)
The impacts of climate changes to cities, which are home to over half of the world´s population, are already being felt. In many cases, the intensive speed with which urban centres have been growing means that little attention has been paid to the role played by climatic factors in maintaining the quality of life. Among the negative consequences of rapid city growth is the expansion of the problems posed by urban heat islands, defined as areas in a city that are much warmer than in other sites, especially in comparison with rural areas. This paper analyses the consistency of the UHI related literature in three stages: first it outlines its characteristics and impacts in a wide variety of cities around the world, which poses pressures to public health in many different countries. Then it introduces strategies which may be employed in order to reduce its effects, and finally, it analyses available tools to systematize the initial high-level assessment of the phenomenon for multidisciplinary teams involved in the urban planning process. The analysis of the literature on the characteristics, impacts, strategies and digital tools to assess on the UHI, reveals the wide variety of parameters, methods, tools and strategies analysed and suggested in the different studies, which does not always allow to compare or standardize the diagnosis or solutions.